Hybrid calibration procedure for structured light field system. (September 2022) - Peng, Shuo; Dong, Liquan; Zhai, Yayu; Zhang, Shaohui; Hu, Yao; Hao, Qun
Highlights: A hybrid calibration method for structured light field system combining stereo vision method and phase to coordinate mapping method. The subview of light field system is treated as pinhole model to build auxiliary Fringe Projection Profilometry. Light ray fitting and plane fitting are implemented to improve the calibration accuracy. Abstract: A typical structured light field system consists of a light field camera and a pattern projector. By combining Fringe Projection Profilometry and light field imaging technology, the phase distribution characteristics of each position and each angle of the scene under test could be obtained, thus providing more information dimensions, and therefore improving the robustness and dynamic range of three-dimensional (3D) measurement. System calibration is a decisive factor for high-efficiency and high precision measurement. However, the complicated structure and working method make the calibration of structured light field system usually costly and cumbersome. In this paper, we propose a hybrid calibration approach combining the flexibility of the stereo vision method and high precision characteristics of the phase-coordinate mapping method. The feasibility of the proposed method has been verified in actual experiments with typical 3D targets.